Resilience through Faith: Exploring the Interplay of Religiosity and Stress Levels among Muslim Undergraduate Students amidst the COVID-19 Pandemic - Mohamad Firdaus Mohamad Ismail; Norfarhana Binti Zawawi; Siti Zuhaidah Shahadan (Asian Journal of Medicine & Health Sciences, 2024)
The COVID-19 pandemic has had a profound effect on societies, individuals, families, and communities around the world. Many individuals struggled to manage their stress due to the panic caused by this outbreak, leading to an absence of tranquillity in their daily lives. Engaging in worship and prayer as coping mechanisms for stress offers advantages for individuals of all backgrounds, including those enrolled in universities. The study aims to determine the level of religiosity and stress among Muslim undergraduate students at the Kuantan campus of the International Islamic University Malaysia (IIUM) and explore the association between these two variables. A quantitative crosssectional study was conducted from May to June 2022 on 249 Muslim undergraduates at IIUM Kuantan Campus. Participants were selected using convenience sampling. All Muslim undergraduate students received an English-language Google Forms questionnaire, which included the Duke University Religion Index (DUREL) and Perceived Stress Scale (PSS-10). Data were analysed using SPSS 27.0. At IIUM Kuantan, Muslim undergraduate students exhibited high levels of religiosity (mean=15.73, SD=3.358) but moderate stress levels (mean=20.71, SD=5.590). Weak and inverse linear correlations were found between stress and Organized Religious Activity (ORA)/ Intrinsic Religiosity (IR) items (r=-0.124 and -0.057) respectively, while a weak, direct linear correlation was found between stress and Non-Organized Religious Activity (NORA) item (r=0.087). However, all three items have insignificant p-values (ORA: p=0.051, NORA: p=0.173, IR: p=0.370); thus, the null hypothesis (H0) cannot be rejected. Most IIUM Kuantan Muslim undergraduates were religious but experienced moderate stress during the COVID-19 pandemic. Despite this, religiosity did not significantly correlate with stress level.